PERKEMBANGAN IPTEK: DAMPAK DAN KONSEKWENSINYA - Wahyono, Poncojari (Jurnal Bestari, 1991)
The Rapid spread of Information give the main rule to widen and strengthen the quantity and quality of science and technology. This product of man power is now seen as characteristics of modern world. Technology, as the real product of science, guides men to two ways of life; condusive and destructive. Indonesia, one of the developing countries, shoul